(untitled) (CIPEEX, 2025)
Introduction: Severe asthma is a chronic airway inflammation with remodeling, hyperresponsiveness, and persistent symptoms, leading to high morbidity. Pulmonary rehabilitation improves ventilatory capacity, reduces symptoms, and modulates inflammation. Physical exercise has important anti-inflammatory effects. Kinins, especially bradykinin, participate in bronchoconstriction and inflammation. Investigating this relationship may broaden therapeutic strategies. Objectives: To evaluate whether pulmonary rehabilitation modulates the levels and expression of kinins and pulmonary kininogen, as well as the levels of pro-inflammatory Th1, Th2, and Th17 cytokines in individuals with severe asthma. Method: Twenty-one patients with severe asthma, diagnosed according to GINA, aged between 20 and 60 years, without comorbidities and under continuous medication for ≥6 months, were included. Exhaled breath condensate samples were collected to quantify pro-inflammatory mediators (IL-1β, IL-5, IL-6, IL-13), anti-inflammatory mediators (IL-1ra, IL-10), pro-fibrotic factors (VEGF, TSLP), and anti-fibrotic factors (relaxin-3, klotho) by ELISA. Normality was assessed by the Kolmogorov-Smirnov test, and comparisons were performed with t-tests, considering p<0.05, using GraphPad Prism 5.0. Results: The results demonstrated that pulmonary levels of the pro-inflammatory cytokines IL-1β, IL-5, IL-6, IL-13 (p<0.01) showed significant reductions after physical training/rehabilitation compared to pre-intervention values. On the other hand, pulmonary levels of the anti-inflammatory cytokines IL-1ra and IL-10 (p<0.01) showed significant increases after physical training/rehabilitation compared to pre-intervention values. Similarly, the levels of the pro-fibrotic factors VEGF and TSLP (p<0.001) showed significant reductions after physical training/rehabilitation compared to pre-intervention values, while the levels of the anti-fibrotic factors relaxin-3 and klotho (p<0.01) showed significant increases after physical training/rehabilitation compared to pre-intervention values. Conclusion: Pulmonary rehabilitation decreases pulmonary inflammation in patients with severe asthma by regulating pro- and anti-inflammatory as well as pro- and anti-fibrotic mediators, indicating its potential in controlling disease progression.